2014
DOI: 10.1590/1678-7225
|View full text |Cite
|
Sign up to set email alerts
|

Glicerina bruta para codornas de corte, de um a 14 e de 15 a 35 dias de idade

Abstract: Três experimentos foram conduzidos para determinar o valor nutritivo da glicerina bruta (GB), bem como verificar o desempenho de codornas de corte alimentadas com essa fonte alternativa de alimento. No experimento I, foram utilizadas 75 codornas, distribuídas em delineamento inteiramente ao acaso (DIC), com três tratamentos e cinco repetições. Os tratamentos consistiram de uma ração referência (RR) e duas rações teste (RT), e a GB substituiu a RR em níveis de oito e 12%. O valor estimado de energia metabolizáv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(6 reference statements)
0
6
0
1
Order By: Relevance
“…This ingredient has been attributed the characteristic of improving the texture (PASQUETTI et al, 2014) and palatability (SILVA et al, 2013) of feeds, which are aspects responsible for increased feed intake. However, some studies have reported interference of some substances contained in crude glycerin that may lead to limitations to intake, such as the sodium content (GUERRA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This ingredient has been attributed the characteristic of improving the texture (PASQUETTI et al, 2014) and palatability (SILVA et al, 2013) of feeds, which are aspects responsible for increased feed intake. However, some studies have reported interference of some substances contained in crude glycerin that may lead to limitations to intake, such as the sodium content (GUERRA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Alguns trabalhos com frangos de corte (Guerra et al 2011, Silva et al 2012, Henz et al 2014, poedeiras (Swiatkiewicz & Koreleski 2009, Duarte et al 2014) e codornas (Pasquetti et al 2014) vem sendo desenvolvidos, entretanto a composição das glicerinas utilizadas em cada estudo é bastante variável, principalmente em relação aos teores de sódio, cloro e metanol, o que é consequência do processamento do óleo ou gordura para obtenção do biodiesel, sendo muitas vezes contraditórias as definições aplicadas à glicerina resultante desse processo.…”
Section: Introductionunclassified
“…This is a response that contrasts with the results obtained in this study until week 28 since the use of diets with higher energy resulted in lower feed consumption, which reduced costs and increased profitability. In this study, glycerin inclusion in diets of transition phase of laying hens did not affect the costs, however, Pasquetti et al (2014), observed a linear reduction in quail production costs with the use of crude glycerin, while Batista et al (2013) and Avellaneda et al (2018), found that the inclusion of refined glycerin negatively affects production costs.…”
Section: Treatmentmentioning
confidence: 47%